Efektivitas Penggunaan Platform Quizizz dalam Meningkatkan Minat dan Pemahaman Konsep Matematika - M. Ardiansyah (Universitas Indraprasta PGRI Jakarta, 2022)
This research is a survey conducted on 20 students of SMP Ma`arif in the academic year 2020/2021. The sampling technique used was purposive sampling. The subjects studied were about learning interest and the level of understanding of mathematical concepts about the arithmetic sequence of students. The Quizizz platform is a platform that can be used to find out how much students understand mathematical concepts. This research was conducted on 20 students of class VIII SMP Ma`arif Jakarta using 10 conceptual questions presented by the Quizizz platform. The results of the analysis showed that the overall conceptual understanding of students was 56%. This shows that the level of understanding of the concepts that students have is in the medium.